A corespondence analysis of sources of information used by festival visitors - Shanka, Tekle; Taylor, Ruth (Cognizant communication corporation, 2004)
Information sources used by festival visitors need to be examined due to the increasing competition within the events sector as a result of growth in the number and size of events being staged. The article provides an analysis of a visitor profile of a major wine festival staged in the Swan Valley wine region of Western Australia (WA). A survey was conducted over the five weekends of the staging of the 2002 festival. Data were analyzed using correspondence analysis techniques to underpin the underlying dimensionalities of the sources of information based on age groups, group composition, and usual place of residence of intrastate, interstate, and international visitors. Results indicate that the most common source of festival information was personal through word-of-mouth across all visitor groups. Other sources of information that also had some significance include newspapers and radio. The results provide information for developing a theoretical framework for events information search behavior, and managerial implications for festival organizers are presented.